2011
DOI: 10.1002/cbic.201100576
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism‐Oriented Redesign of an Isomaltulose Synthase to an Isomelezitose Synthase by Site‐Directed Mutagenesis

Abstract: An isomelezitose synthase was redesigned out of the sucrose isomerase from Protaminobacter rubrum for the synthesis of isomelezitose (6-O(F)-glucosylsucrose), a potential nutraceutical. The variants F297A, F297P, R333K, F321A_F319A and E428D catalyze the formation of isomelezitose in up to 70 % yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…This result is consistent with the conclusion that Phe256 and Phe280 in MutB were essential for product specificity [13,25]. Gorl et al observed a similar result that mutagenesis of Phe297 and Phe321 in SmuA abolished the isomaltulose synthesis activity [48]. …”
Section: Resultssupporting
confidence: 88%
“…This result is consistent with the conclusion that Phe256 and Phe280 in MutB were essential for product specificity [13,25]. Gorl et al observed a similar result that mutagenesis of Phe297 and Phe321 in SmuA abolished the isomaltulose synthesis activity [48]. …”
Section: Resultssupporting
confidence: 88%
“…As previously mentioned, several microbial α‐glucosidases has been already used to produce isomelezitose, a rare trisaccharide found in honey, which shows potential nutraceutical and prebiotic properties (Görl et al , ). However, and as far as we know, the obtained yields when using native enzymes or cellular extracts were lower than those reported in this work.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Munir and Vogel () patented the synthesis of isomelezitose using immobilized cells of Protaminobacter and 50ºC with yields close to 11% of total sugars. Besides, Görl et al () transformed a sucrose isomerase into an isomelezitose synthase, obtaining a protein variant by mutation that yielded 70% of isomelezitose using 100 g l −1 sucrose, but this amount was calculated based on sucrose consumed (~ 32%) instead of the total sucrose added to the reaction mixture, which means to produce about 22.4 g l −1 of this trisaccharide. More recently, Côté et al () obtained an engineered glucansucrase from the bacteria Leuconostoc mesenteroides that produced isomelezitose very efficiently using ~ 800 g l −1 sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…Although several uses for isomelezitose have been proposed, including prebiotics [7] and pharmaceutical excipients [Backström et al, 1999, Powder formulations containing melezitose as a diluents, US Patent 6,004,574. ], applications are limited due to the high cost and relative scarcity of this compound.…”
Section: Streptococcus Sobrinus 6715 Gtfi Variantsmentioning
confidence: 99%
“…], applications are limited due to the high cost and relative scarcity of this compound. Isomelezitose has been isolated in small amounts from several enzymatic reaction mixtures [1,4,5], but only one instance of a high-yielding synthesis has been reported [7]. In that example, the yield was reportedly over 70% from sucrose, but that number was calculated from the amount of sucrose consumed, not from the total sucrose added to the reaction.…”
Section: Streptococcus Sobrinus 6715 Gtfi Variantsmentioning
confidence: 99%